Beyond Safety Training Embedding Safety in Professional Skills (SpringerBriefs in Safety Management,, 2018)
This book is open access under a CC BY 4.0 license. This book investigates why, despite more and more resources devoted to safety training, expectations are not entirely met, particularly in the industrial sectors that have already achieved a high safety level. It not only reflects the most precious viewpoints of experts from different disciplines, different countries, with experiences in various industrial fields at the cutting edge of theories and practices in terms of safety, professionalization and their relationships. It also consolidates the positioning of the Foundation for an Industrial Safety Culture, highlighting what is currently considered at stake in terms of safety training, taking into account the system of constraints the different stakeholders are submitted to. It reports some success stories as well as elements which could explain the observed plateau in terms of outcome. It identifies some levers for evolution for at-risk industry and outlines a possible research agenda to go further with experimental solutions.